Histochemical and physiological studies on the Rat’s liver during embryonic life and after birth - Aboalhaj, Abdusalam M.; Gheth, Ebtesam M. M.; El-Gharbawy, Saad M. S.; El-Durssi, Ibrahim S.H. (Al-Mukhtar Journal of Sciences, 2008)
In this study, the development of the rat's liver was investigated during the embryonic life using 39 fetuses ranged from 9-21 days of age, and 39 rats with ages from one day after birth to four months. The result of the histochemical investigation showing positive Periodic acid schiff (PAS) reaction of hepatic cells from the 20th day of fetal life. These reactions increased with the advancement of age and continued after birth. On the other hand, these hepatic cells showed negative reaction with alcian blue and aldahyed fuchsin stains. Glycogen granules began to appear in the hepatic cells in the last day of intrauterine life. These granules decreased in intensity and quantity in the inner parts of liver as we go far from the capsule. After birth, these granules increased in amount and staining affinity where it distributed allover the liver; in the peripheral and central parts. There was no difference in the concentration of albumin in all the studied ages.